Housing Options for Individuals Experiencing Chronic Homelessness: Subsidized and Non-Subsidized Housing Outcomes among Pathways to Independence Participants. Issue 46 (2nd September 2020) - Brown, Molly; Mihelicova, Martina; Collins, Kelly; Cummings, Camilla; Ponce, Allison
Abstract: Research on housing interventions for individuals experiencing chronic homelessness has largely focused on permanent supportive housing (PSH); however, an array of housing options to support the diverse needs and goals of chronically homeless people is necessary. A dearth of research exists on the non-subsidized private rental market as an option for people who are chronically homeless. The objective of this observational study was to identify sociodemographic and health predictors of attaining non-subsidized housing compared to other outcomes among a sample of 273 individuals who participated in Pathways to Independence (PTI). PTI was a homeless service program that connected chronically homeless participants with options beyond PSH, including private market housing. Results indicated that being younger, male, and employed were associated with greater odds of being housed without a subsidy compared to PSH. Having disability income and being in fair or poor health were associated with greater odds of attaining non-subsidized housing compared to remaining homeless. Findings suggest that private market housing may be an option for individuals who participate in services supporting income and employment attainment. While this study focused on immediate housing outcomes, future research is needed to examine long-term outcomes of formerly chronically homeless individuals residing in non-subsidized housing.